SIFAT PENGGERGAJIAN DAN PENGERJAAN BEBERAPA JENIS KAYU HTI - Dede Rohadi; Bakir Ginoga (Jurnal Penelitian Hasil Hutan, 1994)
This paper  reports  the studies  on sawmilling  woodworking properties  of 3 plantation  wood species.  derived from some plantation areas  in Java,  Logs of K.emiri  (Aleurites molluccana). tusam (Pinus merkusii) and Piaus oocarpa were sawn using a 44 inch bandsaw  to produce various size of boards. Following drying to approximately 1 5% of moisture content. the boardh were observed for their machining properties. The dried boards were processed further  into varaous end products and furnitures.Sawmilling trials shorwed that the average  sawn timber recoveries for  the respective species were 45%, 60% and 73%. regardless to the limited length and  width of  the resulted boards from  the sawmilling process, which were due  to the  small  log diameters,  a satisfactory  jointing  board can be  produced  through the application  of finger  and edge jointing machines.All  of  the species showed to have good  machining  properties and good  workability. Either  the fresh  logs or wood cants can beutilized for  producing  various  tuming products.  handicrafts  or even furnitures such as tables and chairs.  The  study  showed the potential utilization  of plantation  materials for various end products.